Impact of Freshwater Discharge on the Carbon Uptake Rate of Phytoplankton During Summer (January–February 2019) in Marian Cove, King George Island, Antarctica - Kim, Bo Kyung; Jeon, Misa; Joo, Hyoung Min; Kim, Tae-Wan; Park, Sang-Jong; Park, Jisoo; Ha, Sun-Yong (Frontiers in Marine Science, 2021)
Rapidly changing conditions in high-latitude coastal systems can significantly impact biogeochemical cycles because these systems are strongly influenced by freshwater discharged from melting glaciers and streams on land. Generally, Antarctic coastal areas are considered high-productivity areas in which phytoplankton growth prevails under various environmental conditions (e.g., oceanographic and meteorological conditions). This study provides carbon uptake rates of phytoplankton in Marian Cove during summer (January-February 2019). Daily depth-integrated carbon uptake varied greatly and averaged 0.8 g C m–2 day–1, with a maximum of 4.52 mg g C m–2 day–1 recorded on 14 January. Similarly, the observed biomass standing stocks were very high (up to 19.5 mg m–3 chlorophyll a) and were dominated by microphytoplankton (20–200 μm), representing 84% of total chlorophyll a (chl-a). The depth-integrated chl-a and carbon uptake decreased from outer to inner areas (close to the glacial front) in the cove. As the austral summer progressed, the freshening of the surface waters coincided with high water stability and suspended material and with low productivity when nanophytoplankton were present (2–20 μm; >60%). These findings suggest that both photosynthetically active radiation penetrating the water column and enhanced turbidity control light availability for phytoplankton, as well as their community compositions.